Are There Height‐Dependent Differences in Subclinical Vascular Disease in Hypertensive Patients?. Issue 1 (5th November 2013) - Ferriol, Caterina; Tremols, Susanna; Jimenez, Carmen; Tura, Anna; Sanmartín, Maria; Pagès, Núria; Rodríguez‐Poncelas, Antonio; Paz‐Bermejo, Marco; Saez, Marc; Coll‐de‐Tuero, Gabriel
<x xml:space="preserve">Abstract</x> The aim of the study was to determine whether there are differences in subclinical vascular disease (SVD) in hypertensive patients in relation to height. A total of 922 hypertensive, newly diagnosed, treatment‐naive patients were included. Physical examination was conducted, with renal function, electrocardiography, and retinography. Patients were distributed according to quartiles of height and sex. Multivariate analysis adjusted for age, sex, and body mass index showed an association between height above the mean and fasting glucose (odds ratio [OR], 1.04; 95% confidence interval [CI], 1.02–1.06), high‐density lipoprotein cholesterol (OR, 0.96; CI, 0.92–0.99), triglycerides (OR, 1.07; CI, 1.01–1.15), and left ventricular hypertrophy (LVH) (OR, 1.57; CI, 1.10–2.24). The authors found an inverse association between arteriole‐to‐venule ratio and height above the mean (OR, 0.97; CI, 0.94–0.99). There are differences in the SVD of hypertensive patients in relation to height. Tall stature is associated with LVH while short stature is associated with increased microvascular involvement. Detection of SVD in hypertensive patients should consider the height.